Structural basis of arrestin-3 activation and signaling. Issue 1 (December 2017) - Chen, Qiuyan; Perry, Nicole; Vishnivetskiy, Sergey; Berndt, Sandra; Gilbert, Nathaniel; Zhuo, Ya; Singh, Prashant; Tholen, Jonas; Ohi, Melanie; Gurevich, Eugenia; Brautigam, Chad; Klug, Candice; et al.
Abstract A unique aspect of arrestin-3 is its ability to support both receptor-dependent and receptor-independent signaling. Here, we show that inositol hexakisphosphate (IP6 ) is a non-receptor activator of arrestin-3 and report the structure of IP6 -activated arrestin-3 at 2.4-Å resolution. IP6 -activated arrestin-3 exhibits an inter-domain twist and a displaced C-tail, hallmarks of active arrestin. IP6 binds to the arrestin phosphate sensor, and is stabilized by trimerization. Analysis of the trimerization surface, which is also the receptor-binding surface, suggests a feature called the finger loop as a key region of the activation sensor. We show that finger loop helicity and flexibility may underlie coupling to hundreds of diverse receptors and also promote arrestin-3 activation by IP6 . Importantly, we show that effector-binding sites on arrestins have distinct conformations in the basal and activated states, acting as switch regions. These switch regions may work with the inter-domain twist to initiate and direct arrestin-mediated signaling. While arrestins are mainly associated with GPCR signaling, arrestin-3 can signal independently of receptor interaction. Here the authors present the structure of arrestin-3 bound to inositol hexakisphosphate (IP6 ) and propose a model for arrestin-3 activation.